Effects of patch size on mammal biodiversity in lowland and hill dipterocarp forests - Afiqah Abd Rahim (2017)
Forest fragmentation has been one of the main issues in urban landscape due to anthropogenic activities. It leads to remnants of forest patches, which were originally large and continuous forest. Forest fragmentation will adversely impact on forest fauna diversity especially the mammals. This study investigated species richness and abundance of mammals within fragmented urban forest in the state of Selangor. Three remnants of forest reserves located in the midst of an urban landscape that vary in size were chosen which are Ayer Hitam Forest Reserve (AHFR), Bangi Forest Reserve (BFR), and Sungai Lalang Forest Reserve (SLFR). Camera-trapping survey was used as a method. Twenty sampling points were mounted in each urban forest patches. BFR has been recorded has the highest mammal species richness and abundance compare to other sites. This result is somewhat counterintuitive with past study that said forest size is the major factor that influenced the species richness of mammals. The main reason for the outcome is because of human disturbance and impact of the edge effect. Taken together, species richness and abundance were not affected by forest size. However, further studies need to be carried out at a larger experimental scale to test this theory.